The Relationship between Parkin and Protein Aggregation in Neurodegenerative Diseases - Khandelwal, Preeti J.; Moussa, Charbel (Frontiers in Psychiatry, 2010)
The most prominent changes in neurodegenerative diseases are protein accumulation and inclusion formation. Several neurodegenerative diseases, including Alzheimer’s, the Synucleinopathies and Tauopathies share several overlapping clinical symptoms manifest in Parkinsonism, cognitive decline and dementia. As degeneration progresses in the disease process, clinical symptoms suggest convergent pathological pathways. Biochemically, protein cleavage, ubiquitination and phosphorylation seem to play fundamental roles in protein aggregation, inclusion formation and inflammatory responses. In the following we provide a synopsis of the current knowledge about protein accumulation and astrogliosis as a common denominator in neurodegenerative diseases, and we propose insights into protein degradation and anti-inflammation. We review the E3-ubiquitin ligase and other possible functions of parkin as a suppressant of inflammatory signs and a strategy to clear amyloid proteins in neurodegenerative diseases.